Research on scanning characteristics of periodically-nonuniform dielectric plate - Hoblyk, Viktor; Pavlysh, Volodymyr; Nychai, Iryna (Видавництво Львівської політехніки, 2012)
In this paper scanning capabilities of periodicallynonuniform dielectric plate are tested in order to create scanning antennas and radiative devices for the millimetric and optical ranges waves.
Keywords: modulated dielectric plate; scanning antennas; optical devices